Um estudo da experiência dos usuários de Internet banking de um banco público brasileiro - Hellen Oliveira da Silva, Thiago; da Silva Juliani, Jeferson; Soares Mendes, Marília; Rosemberg Maia de Carvalho, Carlos (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
Banking systems have been a frequent concern between customers and companies, since the number of financial transactions carried out by the Internet has increased considerably. This study investigated the experience of internet banking users of a Brazilian bank. Techniques such as interviews, access log analysis, user journeys and usability testing were applied to identify the elements of the user experience using a generic model. From the studies carried out, it was verified that the characteristic users of the service had difficulty or are unable to use all the essential services of internet banking and are necessary design improvements of current interface.